Small Hydropower Development Potential in Chechen Republic - Kerimov, I. A.; Gaysumov, M. Ya.; Badaev, S.V.; Batukaev, A. A. (International Journal of Energy Economics and Policy, 2020)
The aim of this study is to examine the issues of energy development and hydroelectric potential utilization of the rivers in the Chechen Republic. One gives a brief description of the river network and performs the hydroelectric potential's calculations of large and small rivers. One estimates the hydroelectric potential at about 4.86 billion. kWh. The share content of hydroelectric resources constitutes 3682.7 kWh per 1 km2 of the territory. We attribute special attention to the potential assessment of rivers within the mountainous part of the territory. The estimated gross potential of mountain rivers alone is 2.4 billion rubles. kWh, and technical-0.55 billion. kWh. One note that the development of small hydropower is an important factor of improvement in regard to the socio-economic conditions of the population's life and territory's energy security. Keywords: hydropower, potential of small rivers, distributed power generation, ecology, sustainable development, hydroelectric power stations, Chechen Republic JEL Classifications: O13, P28, P48,Q42, R11 DOI: https://doi.org/10.32479/ijeep.10491